Izlīguma ietekme uz cietušo un likumpārkāpēju un ieteikumi izlīguma īstenošanas uzlabošanai - Auziņa, Agnese (Latvijas Universitāte, 2015)
Maģistra darba tēma ir „Izlīguma ietekme uz cietušo un likumpārkāpēju un ieteikumi izlīguma īstenošanas uzlabošanai”. Darba autore izvēlējās rakstīt maģistra darbu par šo tēmu, jo tikai sodot personu nav iespējams panākt taisnīgu krimināltiesisko attiecību noregulējumu, un, tā kā Latvija cenšas mainīt savu sodu politiku no brīvības atņemšanas sodiem uz alternatīviem sodiem, lai sekmētu efektīvāku sodu un citu tiesisko līdzekļu piemērošanu, palielinot sabiedrības drošību un veicinot valsts resursu samērīgu izmantošanu noziedzības apkarošanā, izlīgums var būt nozīmīga alternatīva tam.

The topic of the Magistr Thesis is “Recouncilation in Criminal Process influence on victim and offender and recomenndiation for recouncilation procedure improvment. The author of the work decided to write her Magistr Thesis on this subject, because fair provision of criminal justice relations cannot be attained only by punishing a person and reconciliation can serve as a substantial alternative as Latvia aspires to change its penalty politics transforming imprisonment penalties into alternative penalty in order to facilitate more efficient application of penalties and other legal measures, while increasing the public safety and enabling reasonable use of state resource for fighting crime. Therefore the aim of the Thesis is to explore the development of reconciliationestablishment and judicial effects of its attainment, as well as its efficiency within the framework of Latvian criminal proceedings law.
Recouncilation in Criminal Process influence on victim and offender and recomenndiation for recouncilation procedure improvment
Keywords: Juridiskā zinātne